2014
DOI: 10.1017/s1368980014000561
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated fat intakes and mental health outcomes in young women from the Australian Longitudinal Study on Women’s Heath

Abstract: Results: Adjusted logistic regression analyses found statistically significant associations between higher intakes of α-linolenic acid and decreased likelihood of depressive symptoms indicated by the ten-item Center for Epidemiological Studies Depression Scale (CESD-10; OR = 0·77; 95 % CI 0·60, 0·99; P = 0·040) and the Short Form Health Survey (SF-36) mental health subscale (OR = 0·73 95 % CI 0·56, 0·96; P = 0·024). Furthermore, higher intakes of n-6 fatty acids (OR = 0·96, 95 % CI 0·93, 0·99; P = 0·019) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
(70 reference statements)
1
17
2
Order By: Relevance
“…However, over the long term (8–52 weeks), participants on the high-fat diet reverted to baseline levels of anxiety and depression. In a large Australian epidemiological study, Daley, Patterson, Sibbritt, and MacDonald-Wicks (2015) reported results that contradict those of both the present study and Brinkworth’s study, finding that participants who increased intakes of n-3 (linoleic) and n-6 fatty acids had decreased anxiety.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, over the long term (8–52 weeks), participants on the high-fat diet reverted to baseline levels of anxiety and depression. In a large Australian epidemiological study, Daley, Patterson, Sibbritt, and MacDonald-Wicks (2015) reported results that contradict those of both the present study and Brinkworth’s study, finding that participants who increased intakes of n-3 (linoleic) and n-6 fatty acids had decreased anxiety.…”
Section: Discussioncontrasting
confidence: 99%
“…Yet Sublette et al (2006) found that low fatty acid levels were associated with depression in medication-free patients with suicidal tendencies. This finding was similar to those of other studies in which increased intakes of n-3 and n-6 fatty acids were associated with a decreased likelihood of depression (Daley, Patterson, Sibbritt, & MacDonald-Wicks, 2015; Stahl et al, 2014). A recent meta-analysis of data from 23 different studies involving almost 5,000 participants with different oxidative stress markers suggested that oxidative stress is increased and antioxidant defenses are decreased in depression (Palta, Samuel, Miller, & Szanton, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Several environmental factors have been associated with the increasing prevalence of mental health problems among youth, including insufficient PA, 21 unhealthy diet, 22 high frequency of internet use, 23 long duration of sedentary time 24 25 and leisure-time screen use. 26 Given that young people at college have higher educational levels and are likely to possess more electronic products, they may be more susceptible to ST exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, attention has turned to the potential role of modifiable lifestyle behaviours, such as diet, in the development of common mental health disorders. Studies examining diet-mental health relationships focused on specific micronutrients such as folate and B-vitamins [2,3,4], macronutrients such as fatty acids [5,6], and single food items and groups such as tea, fruit, vegetables and fish [6,7,8] have added to the knowledge base. However, observing the effect of individual nutrients and foods may not be representative of the impact of whole diet on mental health, as diet is a complex combination of foods and nutrients which are not consumed in isolation.…”
Section: Introductionmentioning
confidence: 99%